Finding advanced characteristics of student population participating in the study of knowledge - Japelj Pavešić, Barbara (Šolsko polje, 2012)
In recent years, comparative studies in education have developed also in reporting their results. Some limitations to the analysis and interpretations have been found and discussed amongst researchers leading them to find new methodology, which can reliably explain collected data. The most problematic are causal effects, which are hard to find and complex to interpret. However, since the policy makers need explicit ideas for changes in the educational system, new methodology has entered into the field of education from other areas. One of them is clustering, specifi cally adapted to symbolicor nominal data from educational studies, which can serve to help explain complex links amongst the factors and, as an additional step, to narrow the fi nding of reliable causal relations. In this work, the application of such clustering on the Slovene data from the international study of the measurement of mathematical knowledge amongst students before starting university, TIMSS Advanced has been shown.
Keywords: advanced mathematics; TIMSS; zahtevnejši programi; coverage index; clustering; matematika; mathematics; preverjanje znanja; student background; learning environment; dijaki; učno okolje; vzgoja in izobraževanje; education; pedagoško raziskovanje; raziskave